EFEKTIVITAS METODE PEMBELAJARAN GASING DALAM MENINGKATKAN KEMAMPUAN OPERASI PERKALIAN PADA ANAK DISABILITAS INTELEKTUAL RINGAN - Putri, Mutya Sherinda; Damri, Damri; Nurhastuti, Nurhastuti; Tsaputra, Antoni; Zupiani, Mardhatillah (STKIP Pesisir Selatan, 2025)
Children with intellectual disabilities generally experience obstacles in their academics, one of which is in mathematics lessons, namely performing multiplication operations at school. Based on the results of assessments that have been carried out in special schools, there are children who cannot perform multiplication operations from 1 to 10. The results of the identification and assessment conducted by researchers are based on the identification instrument for children with special needs and numeracy assessments. The purpose of this study is to test the effectiveness of the GASING method (Easy, Fun, and Enjoyable). The selection of research subjects uses the identification instrument for children with special needs and numeracy assessments. This study uses a single subject research form with a multiple baseline cross variable design. The research subject is one person with the aspect of performing multiplication operations from 1 to 10. Data were collected through performance tests and the tools used are multiplication operation performance test instruments and data processing used are percentages. Data analysis is made in the form of visual graphic analysis consisting of analysis within conditions and analysis between conditions. The results of the study show an increase in performing multiplication operations from 1 to 10 after being given the GASING method. It is recommended that teachers use the GASING method to help children perform multiplication operations.